Digital Health Technology-Based Patient-Centered Seamless Care Model for Chronic Disease Management after Cancer Treatment - Back, Kyoungyeon; Kim, Nayeon; Kim, Kyuwoong; Hwangbo, Yul; Chang, Yoon Jung (Healthcare informatics research, 2022)
KCI Citation Count: 0